2019
DOI: 10.1021/acs.inorgchem.9b01278
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of [4Fe-4S] Cluster Assembly on Eukaryotic Mitochondrial and Cytosolic Aconitase

Abstract: Iron−sulfur (Fe−S) clusters are common prosthetic groups that are found within a variety of proteins responsible for functions that include electron transfer, regulation of gene expression, and substrate binding and activation. Acquisition of a [4Fe-4S] cluster is essential for the functionality of many such roles, and dysfunctions in Fe−S cluster synthesis and trafficking often result in human disease, such as multiple mitochondrial dysfunctions syndrome. While the topic of [2Fe-2S] cluster biosynthesis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Of these three, only the N6-acetyl lysine would fall outside the mitochondrial targeting sequence, and it was found using structural modeling that the nucleotide portion of SAM would fall a dis- Inasmuch as the auxiliary cluster site appeared to be almost completely occupied in the as-isolated form of the enzyme, cluster delivery must have taken place at the reducing site to yield the fully reconstituted and active form of human LIAS. Because formation of the [4Fe-4S] cluster at the reducing site is mediated by the consecutive delivery of clusters from [2Fe-2S] donors, the second step, forming the final [4Fe-4S] center, must be rate limiting and is consistent with prior observations for the [4Fe-4S] cluster protein, aconitase [24]. The highest apparent second order rate constant for cluster reconstitution was demonstrated by full-length ISCA2, followed by the truncated, but not necessarily physiological form of ISCA2, and then ISCU (Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Of these three, only the N6-acetyl lysine would fall outside the mitochondrial targeting sequence, and it was found using structural modeling that the nucleotide portion of SAM would fall a dis- Inasmuch as the auxiliary cluster site appeared to be almost completely occupied in the as-isolated form of the enzyme, cluster delivery must have taken place at the reducing site to yield the fully reconstituted and active form of human LIAS. Because formation of the [4Fe-4S] cluster at the reducing site is mediated by the consecutive delivery of clusters from [2Fe-2S] donors, the second step, forming the final [4Fe-4S] center, must be rate limiting and is consistent with prior observations for the [4Fe-4S] cluster protein, aconitase [24]. The highest apparent second order rate constant for cluster reconstitution was demonstrated by full-length ISCA2, followed by the truncated, but not necessarily physiological form of ISCA2, and then ISCU (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…These were chosen because they had been implicated in the trafficking of clusters to LIAS based on experimental data or observations found in patients with NKH and MMDS [19], or to the reconstitution of other [4Fe-4S]-containing proteins [21,22]. Both full-length and truncated versions of ISCA2 were utilized as [2Fe-2S] donors to further compare the reactivity between the two constructs characterized in previous reports [23,24]. A BOLA3-GLRX5 heterodimer has also been shown to have [2Fe-2S] cluster trafficking ability and has been indirectly implicated in cluster transfer to LIAS [19,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, our in vitro results are consistent with a nonessential role for NFU proteins in plant mitochondria. Moreover, our cluster transfer studies also support mitochondrial aconitase maturation via intact [4Fe-4S] 2+ cluster transfer, rather than a mechanism involving sequential transfer of two [2Fe-2S] 2+ clusters followed by in situ reductive coupling, as recently proposed for human mitochondrial and cytosolic aconitase ( 57 ).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, Mössbauer and NMR studies have also demonstrated that reconstituted human NFU1 exclusively contains a [4Fe-4S] 2+ cluster ( 53 , 54 ). This reinterpretation necessitates a major reevaluation of the results and conclusions made by Cowan and co-workers ( 55 , 56 , 57 , 58 , 59 ) about human NFU1. The discovery that both NFU4 and NFU5 are [4Fe-4S] 2+ cluster-binding proteins, coupled with our inability to assemble a [2Fe-2S] 2+ cluster on NFU4 and NFU5 either by reconstitution or cluster transfer from [2Fe-2S]-ISCA1a/2 or [2Fe-2S]-GRXS15, is in accord with the statement that all mitochondrial NFU proteins function in [4Fe-4S] 2+ cluster trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation